HUBUNGAN ANTARA PENGETAHUAN TENTANG ROKOK, TEMAN SEBAYA, ORANG TUA YANG MEROKOK, DAN IKLAN ROKOK TERHADAP PERILAKU MEROKOK PADA MAHASISWA AKADEMI KESEHATAN X DI RANGKASBITUNG - Sarma Eko Natalia Sinaga (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2016)
This research attempted to determine the relationship among knowledge about smoking, peer group smoking behavior, parental smoking, , advertising influence and smoking behavior of Health Academy X in Rangkasbitung. The study was conducted with quantitative approach and used cross-sectional research design into total 94 (ninety-four) respondents. The result of the bivariate analysis using Chi-square test shows a significant relationship among knowledge about smoking (p = 0.004,? ? 0.05), peer group smoking behaviour (p = 0.000, ? ? 0.05) and smoking behaviour. Based on this research, is it recommended that lecturer enchance giving guidance to student about the bad effects of smoking, and impose a stict regulatin over smoking upon student. Parents need to give their children some understanding about the dangers of smoking. Keywords : Smoking Habit, Smoking Behavior, Teenagers